DUAL-OBJECTIVE ORDER SEQUENCING IN A PUT-WALL-BASED PICKING STATION - Park, Seung Won; Kim, Kwang-Tae; Kim, Kyung Min (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The growing e-commerce market has forced distribution companies to provide faster and more accurate delivery services. The order-picking process is the most time-consuming and labor-intensive of the logistics processes carried out in a distribution center. This study considers an order sequencing problem in a put-wall-based picking station. We introduce the problem of distributors aiming to optimize the order-picking sequence to minimize the total dwell time of SKUs as well as the maximum number of SKUs dwelling at the picking station. To tackle this problem, we propose a three-solution approach involving mixed integer nonlinear programming (MINLP), mixed integer linear programming (MILP), and NSGA-II, a non-dominated sorting genetic algorithm. Additionally, we conduct a comparative analysis and verify the performance capabilities of each approach through numerical experiments.